Isolation, characterization, and antibiotic resistance of Vibrio spp. in sea turtles from Northwestern Mexico - Zavala-Norzagaray, Alan A.; Aguirre, A. Alonso; Velazquez-Roman, Jorge; Flores-Villaseñor, Hector; León-Sicairos, Nidia; Ley-Quiñonez, C. Paul; Hernández-Díaz, Lucio D.; Canizalez-Roman, Adrian (Frontiers in Microbiology, 2015)
The aerobic oral and cloacal bacterial microbiota and their antimicrobial resistance were characterized for 64 apparently healthy sea turtles captured at their foraging grounds in Ojo de Liebre Lagoon (OLL), Baja California Sur, Mexico (Pacific Ocean) and the lagoon system of Navachiste (LSN) and Marine Area of Influence (MAI), Guasave, Sinaloa (Gulf of California). A total of 34 black turtles (Chelonia mydas agassizii) were sampled in OLL and eight black turtles and 22 olive ridley turtles (Lepidochelys olivacea) were sampled in LSN and MAI, respectively from January to December 2012. We isolated 13 different species of Gram-negative bacteria. The most frequently isolated bacteria were Vibrio alginolyticus in 39/64 (60%), V. parahaemolyticus in 17/64 (26%) and V. cholerae in 6/64 (9%,). However, V. cholerae was isolated only from turtles captured from the Gulf of California (MAI). Among V. parahaemolyticus strains, six O serogroups and eight serovars were identified from which 5/17 (29.4%) belonged to the pathogenic strains (tdh+ gene) and 2/17 (11.7%) had the pandemic clone (tdh+ and toxRS/new+). Among V. cholerae strains, all were identified as non-O1/non-O139, and in 4/6 (66%) the accessory cholera enterotoxin gene (ace) was identified but without virulence gene zot, ctxA and ctxB. Of the isolated V. parahaemolyticus, V. cholerae and V. alginolyticus strains, 94.1%, 33.4% and 100% demonstrated resistance to at least one commonly prescribed antibiotic (primarily to ampicillin), respectively. In conclusion, the presence of several potential (toxigenic) human pathogens in sea turtles may represent transmission of environmental microbes and a high-risk of food-borne disease. Therefore, based on the fact that it is illegal and unhealthy, we discourage the consumption of sea turtle meat or eggs in northwestern Mexico.